Uso de hidrogel en el cultivo de pachaco (Schizolobium parahybum) - Diaz Villacis, Pamela Nahomi (2022)
This document deals with the use of hydrogel in the cultivation of pachaco in Ecuador.These trees tend to grow fast and are highly desirable for the production of veneers and for the manufacture of plywood. Hydropolymer-retaining polymers, also called hydrogels or water-retaining polymers, are natural products (derived from starch) or synthetic (derived from petroleum), valued for their capacity to absorb and store water. Brittle when dry, they become soft and elastic. The low availability of water leads the agricultural sector to implement more efficient technological management for the use of water resources, which is why it is sought to learn more about these polymeric gels since they have many benefits and properties, one of them is the absorption and retention capacity of water, are a good alternative since they are aqueous solutions. The conclusions determined that this polymer helps the root of the tree, accumulating, stores water and then slowly transfers it to the plant, until reaching its maximum degree of hydration or swelling index, it has the ability to dissolve solutes, they are friendly to the environment, they last under the ground from 7 to 10 years, they release the water from 30 to 60 days depending on their texture.